ANALYSIS OF NURSING CARE IN DIPSNEA ET CAUSA PATIENTS WITH DEXTRA LUNG TUMORS WITH COMBINATION THERAPY PURSED LIPS BREATHING AND EUCALYPTUS AROMATHERAPY IN THE GARDENA ROOM, RSD DR. SOEBANDI JEMBER - Novi Putri Cahyanti; Ruris Haristiani; Murtaqib Murtaqib; Mustakim Mustakim (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2024)
Introduction: Lung tumor is a pathological disease that attacks the lungs with the appearance of abnormal cells and one of the symptoms is shortness of breath. The emergence of shortness of breath can cause the supply of oxygen throughout the body to be disrupted. Purpose: This study aim to giving combination therapy of Pursed Lips Breathing and Eucalyptus aromatherapy is to reduce the patient's shortness of breath. Methods: This research is a case study to evaluate interventions given to patients with lung tumors packaged in nursing care. Intervention is given 2x every day for 5-15 minutes for 4 days. Success indicator is measured by oxygen saturation. Result: The results showed that the intervention given for 4 days of clients shortness of breath decreased as evidenced by SpO2 86% to 93%. Discussion: Pursed Lips Breathing exercise will increase the movement of the diaphragm which will add volume to the lungs, with the inspiratory phase causing a decrease in muscle workload and a long expiratory phase causing residues to decrease thereby increasing gas exchange. Giving eucalyptus aromatherapy containing essential oils by dropping it in hot water can change eucalyptus essential oil in aerosol form so that it reaches the respiratory organs and is deposited in the lungs and complaints of shortness of breath can be reduced. Conclusion: The decrease in shortness of breath showed that the combination therapy intervention of Pursed Lips Breathing and Eucalyptus aromatherapy was effective in reducing the degree of shortness of breath in lung tumor patients.